2016
DOI: 10.18823/asiatefl.2016.13.2.3.102
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Beliefs About Task-Based Language Teaching in Japan

Abstract: As task-based language teaching (TBLT) has grown in popularity in many Asian EFL countries, it has sometimes been the target of criticism from locally situated researchers and teachers, who question its appropriateness for such contexts (Burrows, 2008), often in contrast to more traditional methods, such as the "presentation, practice, production" (PPP) approach (Sato 2009). Partially in response to this criticism, the Task Based Language Learning Special Interest Group (TBLSIG) of the Japanese Association for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Yet there has been very little work done on the beliefs of teachers who are actually carrying out TBLT in foreign language classrooms in Japan. Harris (2016) outlined a survey study of 78 teachers based in Japan who are using or previously used a TBLT approach. Results showed that many of these teachers believed common criticisms of TBLT to be misplaced, and that with certain adaptions, TBLT can be successfully implemented in Japan.…”
Section: The Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet there has been very little work done on the beliefs of teachers who are actually carrying out TBLT in foreign language classrooms in Japan. Harris (2016) outlined a survey study of 78 teachers based in Japan who are using or previously used a TBLT approach. Results showed that many of these teachers believed common criticisms of TBLT to be misplaced, and that with certain adaptions, TBLT can be successfully implemented in Japan.…”
Section: The Contextmentioning
confidence: 99%
“…The idea of providing scaffolded support for students new to TBLT is something that has been proposed by TBLT researchers and practitioners in the past (Harris, 2016;Wicking, 2009;Widodo, 2015).…”
Section: Common Criticisms Regarding the Use Of Tblt In Japan And Asiamentioning
confidence: 99%
“…Thus, these issues can be solved by exposing teachers to more TBLT training and techniques in order to help teachers construct positive perceptions of TBLT implication in the Spanish EFL classrooms. Thus, the more teachers' confidence is high the more learners' active participation in a task-based lesson increases and teaching starts to shift toward more learner-centered teaching (Burdett, 2003;Harris, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies show the success story of the application of the Task-Based Syllabus in ELT worldwide. Harris (2016), conducting research in Japan, concludes that Task-Based Language Teaching (TBLT) is a powerful tool for teaching English. Cutrone & Beh (2018), also investigating the application of TBLT in Japan, conclude that it has a positive impact on learners and suggest its application in Japan.…”
Section: Proposed Syllabus Design For Students Of Medicine 421 Syllab...mentioning
confidence: 99%